Health System Trust and Compliance with COVID-19 Restrictions - Joan Costa-Font; Cristina Vilaplana-Prieto (Institute of Labor Economics (IZA), 2023)
We examine the extent to which exposure to higher relative COVID-19 mortality (RM), influences health system trust (HST), and whether changes in HST influence the perceived ease of compliance with pandemic restrictions during the COVID-19 pandemic. Drawing on evidence from two representative surveys covering all regions of 28 European countries before and after the first COVID-19 wave and using a difference in differences strategy together with Coarsened Exact Matching (CEM), we document that living in a region with higher RM during the first wave of the pandemic increased HST. However, the effect is driven by individuals over 45 years of age, and the opposite is true among younger cohorts. We find that a higher HST reduces the costs of complying with COVID-19 restrictions, but only so long as excess mortality does not exceed the average by more than 20%, at which point the ease of complying with COVID-19 restrictions significantly declines, offsetting the positive effect of trust in the healthcare system. Our interpretation of the estimates is that RM is interpreted as a risk signal among those over 45, and as a signal of health-care system failure among younger age individuals.
Keywords: I13; Z1; 330; Eurobarometer; lockdown; mortality; healthcare system trust; difference in differences; COVID-19